Analisis Digital Forensik Terhadap Pemeriksanaan Rekaman Closed Circuit Television (CCTV) Sebagai Strategi Kepolisian Daerah Riau Dalam Pengungkapan Kasus Kejahatan - Vindy Sukma Pelia Putri; Rio Tutrianto (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2025)
Forensic sciences are basically any scientific knowledge that is used to reveal criminal incidents objectively and scientifically. Scientific knowledge can be used as a tool to reveal criminal incidents objectively because scientific knowledge is obtained through scientific research so that its truth can be guaranteed scientifically. Digital forensic analysis of examination of Closed Circuit Television (CCTV) recordings is an important strategy in handling crime cases by the police. With CCTV technology increasingly developing, video recordings can be invaluable evidence in investigating and uncovering crimes. Various ways can be done to increase security, one of which is by installing monitoring cameras or what is usually called CCTV (Closed Circuit Television) which is used as a surveillance camera tool. CCTV contains a video recording file that can be used as digital evidence in disclosing a judicial case. Using a qualitative approach by conducting in-depth interviews with sources. This research explains that the combination of CCTV and digital forensic analysis provides a comprehensive and powerful approach in handling crime cases. CCTV provides basic visual evidence, while digital forensics ensures the integrity and accuracy of that evidence, while adding analytical value for deeper investigations. In an effort to study all content to find evidence that will convince the court, digital investigations must find the right solution by searching all electronic devices located at the scene of the crime, from computers, laptops, cell phones, internal networks, the Internet and others to analyze video, audio, and images. This is believed in the Locard Exchange theory to be a form of trace left behind when someone commits a crime in order to uncover the crime that occurred.Keywords can be single words or combinations of words. The number of keywords should be 3-5. These keywords are essential for computerization, facilitating the search for the research title and abstract.